Estimasi Beta Saham Pada Industri Transportasi Di Bursa Efek Indonesia - Alliny Namilana Rambu Hutar; Dhevis L. R. Taka (Universitas Kristen Wira Wacana Sumba, 2015)
This study aims to examine the systematic risk (β) to stock returns in transportation industry in Indonesia. By adding empirical evidence of a systematic risk of beta (β) in the measurement of risk through the theory of Capital Asset Pricing Model (CAPM) to companies in the transportation industry in Indonesia. By using regression tool analysis on sample of 15 companies during the period of 2010-2012, the results show that the systematic risk (β) affect the average stock return of companies in the transportation industry in Indonesia.